2014
DOI: 10.4103/1658-354x.125917
|View full text |Cite|
|
Sign up to set email alerts
|

PONV in Ambulatory surgery: A comparison between Ramosetron and Ondansetron: a prospective, double-blinded, and randomized controlled study

Abstract: Background:postoperative nausea and vomiting (PONV) frequently hampers implementation of ambulatory surgery in spite of so many antiemetic drugs and regimens.Aims:the study was carried out to compare the efficacy of Ramosetron and Ondansetron in preventing PONV after ambulatory surgery.Setting and Design:it was a prospective, double blinded, and randomized controlled study.Methods:124 adult patients of either sex, aged 25-55, of ASA physical status I and II, scheduled for day care surgery, were randomly alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…At other time periods, including the 24–48 hours after surgery, ramosetron was no more effective than ondansetron in prevention of POV: 0–2 hours (RR 0.67, 95% CI 0.11–4.00; P =0.66), 2–6 hours (RR 0.55, 95% CI 0.21–1.47; P =0.24), 2–24 hours (RR 0.37, 95% CI 0.10–1.35; P =0.13), and 24–48 hours (RR 0.51, 95% CI 0.17–1.51; P =0.22, Figure 3 ). We did not include the study by Banerjee et al 22 in our meta-analysis because these authors did not provide detailed PON and POV outcomes. However, their results showed that preoperative administration of a single intravenous dose of ramosetron 0.3 mg was more effective than a single intravenous dose of ondansetron 4 mg in reducing the incidence of PONV in general in the 18 hours after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…At other time periods, including the 24–48 hours after surgery, ramosetron was no more effective than ondansetron in prevention of POV: 0–2 hours (RR 0.67, 95% CI 0.11–4.00; P =0.66), 2–6 hours (RR 0.55, 95% CI 0.21–1.47; P =0.24), 2–24 hours (RR 0.37, 95% CI 0.10–1.35; P =0.13), and 24–48 hours (RR 0.51, 95% CI 0.17–1.51; P =0.22, Figure 3 ). We did not include the study by Banerjee et al 22 in our meta-analysis because these authors did not provide detailed PON and POV outcomes. However, their results showed that preoperative administration of a single intravenous dose of ramosetron 0.3 mg was more effective than a single intravenous dose of ondansetron 4 mg in reducing the incidence of PONV in general in the 18 hours after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…The ten articles listed below,[ 1 2 3 4 5 6 7 8 9 10 ] all with the same corresponding author and published in the Saudi Journal of Anaesthesia from 2014-2018, are being retracted because they have been found to have a number of unattributed sections of content with high rate of similarity from various other articles along with overwhelming evidence of data fabrication. The corresponding author and his institution were contacted and asked to provide the journal with the raw data for these studies but there has been no adequate response within a reasonable timeframe.…”
mentioning
confidence: 99%